THE STATE MANAGEMENT CAPACITY INDEX IN MEXICO: A TOOL FOR MEASURING PUBLIC POLICIES IN LOCAL GOVERNMENTS - Cortes, Mario Eduardo Ibarra; Mballa, Louis Valentin (European Scientific Journal, ESJ, 2015)
The main purpose of this paper is to present the results of the construction of a methodological instrument called the Subnational Local Governance Index (ISGL). This Index was built to contribute to the assessments of institutional capacities of local governments, in order to resolve public problems in Mexico. The construction of the Index was founded on four main features: 1) The lack of public policy in education, health, public services and housing quality, measured by the level of social backwardness, 2) the structure of government and administration, measured by the institutional capacities, 3) the quality of local government, measured by the level of credibility of the citizens through subnational governance and 4) the local financial capacity, measured by the ability to generate income and to manage the public debt. Basically, the following questions have been used to build the Index: What is the level of social backwardness at the local level? What kind of institutional structure exists at the local level? What is the profile of the public policy managers at the local level? What is the capacity to generate income? What is the level of citizens’ confidence in local governance?